2005
DOI: 10.1038/sj.ejhg.5201407
|View full text |Cite
|
Sign up to set email alerts
|

Proopiomelanocortin gene variants are associated with serum leptin and body fat in a normal female population

Abstract: A major quantitative trait locus (QTL) determining leptin levels has been linked to the proopiomelanocortin (POMC) region on chromosome 2. Most studies, based on under 350 lean or obese subjects, have shown no association between POMC SNP 8246 C/T and serum leptin, but significant associations have been reported with RsaI 8246 C/T SNP haplotypes. We have investigated association of four POMC SNPs with body composition and serum leptin in 2758 normal Caucasian female subjects (mean age 47.4712.5 years), from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
4
8
1
Order By: Relevance
“…The results of the present study differed from the family study in a white British population, which found an association between rs1042571 and WHR (Baker et al, 2005). Moreover, studies in the UK (Chen et al, 2005) and with Caucasian Americans (Wang et al, 2012) also found an association between rs1042571 and BMI. Baker et al (2005) found no association between rs1042571 and BMI in a white British population, which agrees with the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the present study differed from the family study in a white British population, which found an association between rs1042571 and WHR (Baker et al, 2005). Moreover, studies in the UK (Chen et al, 2005) and with Caucasian Americans (Wang et al, 2012) also found an association between rs1042571 and BMI. Baker et al (2005) found no association between rs1042571 and BMI in a white British population, which agrees with the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The common variant C8246T (rs1042571), located in the 3'-untranslated region (UTR), was associated with waist-to-hip ratio (WHR) (P < 0.0001) in a family study on a white British population (Baker et al, 2005). Moreover, in the UK, this single nucleotide polymorphism (SNP) was associated with body mass index (BMI) (P = 0.032) and total fat (P = 0.046) in a recessive model (Chen et al, 2005). In Caucasian Americans, Wang et al (2012) found an association between the C8246T variant and BMI (overweight: P = 0.005; obese: P = 0.018; overweight + obese: P = 0.002) but not among African Americans.…”
Section: Introductionmentioning
confidence: 99%
“…Only 2 reports have identified age at puberty QTL in the pig (Rohrer et al, 1999;Cassady et al, 2001) on chromosomes 1, 7, 8, 10, and 12, and SNP in one of these regions on chromosome 10 are possibly associated (Nonneman et al, 2006) with age at puberty. The QTL for leptin concentrations in humans have been identified in the POMC gene, and SNP and POMC haplotypes are associated with circulating leptin, body mass index, BW, and body fat (Hixson et al, 1999;Chen et al, 2005). Liefers et al (2004) identified a polymorphism in LEPR associated with leptin concentration in pregnant heifers.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in the leptin gene and leptin receptor have been associated with fatness traits, feed efficiency, and reproduction in pigs (Jiang and Gibson, 1999;Kennes et al, 2001;Chen et al, 2004;Mackowski et al, 2005). Genomic regions associated with age at puberty in the pig (Rohrer et al, 1999;Cassady et al, 2001) and leptin concentrations in mice and humans (Hixson et al, 1999;Harper et al, 2003;Chen et al, 2005) have been identified. Genetic relationships of fat and leptin with age at puberty may provide an alternative means of selecting for decreased age at puberty.…”
Section: Introductionmentioning
confidence: 99%
“…2 Supplementary support was found in our own observations, in which disturbance of HPA axis functioning under basal and challenged conditions was related to visceral fat accumulation. 8,9 Literature has also shown associations between the SNP BclI and HPA axis functioning; 10 for instance in men, the BclI GG genotype has been associated with increased salivary cortisol concentrations, particularly after stimulation by a standardized lunch, 4 increased cortisol concentrations after a 0AE5-mg dexamethasone suppression test, 4 and a diminished cortisol response to psychosocial stress. Literature has shown an association between common (minor allele frequency of at least 20%) SNPs of the HPA axis and obesity-related characteristics, such as the CG genotype of the glucocorticoid receptor gene (GR) referred to as the 'BclI' polymorphism (rs41423247).…”
Section: Introductionmentioning
confidence: 99%